VD_FINDINFO Pron / 2013 / 192 vom 16. Juli 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE, FRAIS JUDICIAIRES | 109 al. 1 CPC (CH), 122 CPC (CH), 123 CPC (CH), 241 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 1 TFJC (2010)